Antioxidant Enzyme Activity and Malondialdehyde Concentration on Broiler Fed Contain Lauric Acid and Areca vestiaria Giseke - Jola Josephien Mariane Roosje Londok; Sumiati Sumiati; I Komang Gede Wiryawan; Wasmen Manalu (Faculty of Animal Science, Universitas Gadjah Mada, 2018)
The objective of the study was to determine antioxidant enzyme activity and concentration of malondialdehyde on broiler which consumed feed containing lauric acid and natural antioxidant from Areca vestiaria Giseke. The study used 240 day-old chicks of Lohmann MB 202 P strain placed randomly at 24 experimental cage units (10 chickens each) of the litter system. The average temperature of the cage at the study was 25.80 to 32.080 C with relative air humidity rate of 67.69 to 86.20%. The research method followed a Factorial Completely Randomized Design 2 x 4 with 3 replications. The first factor was the source of lauric acid in feed, i.e. conventional coconut oil (CO) and pure lauric acid (LA). The second factor was the source of antioxidant in the form of dosage of Areca vestiaria (AV) and vitamin E supplementation (TF) with four levels of AV, ie 0, 625 mg.kg-1, 1250 mg.kg-1, and TF at a dose of 200 mg .kg-1 feed. Feed and drinking water were given ad libitum. Meat sampling to measure SOD, catalase and MDA was taken at the end of the study by first chickens were fasted for ± 8 hours (overnight). The sample used was right breast meat of experimental male chicken. The data were average from three experimental chickens. The data obtained were analyzed for the variant with the general linear model on MINITAB (version 16), then tested the differences between treatments using Tukey's honestly significant difference (HSD). The results showed that the source of laurate had a significant effect on SOD, catalase, and MDA, while antioxidant concentration significantly decreased SOD and MDA compared with control. The interaction between lauric sources and antioxidant concentrations affected catalase and MDA. The use of coconut oil as much as 3% and antioxidant supplementation of Areca vestiaria Giseke in feed at a dose of 1250 mg kg-1 could decrease lipid oxidation product of meat to produce a healthy food product.